Dynamic Risk Assessment of the Overseas Oil and Gas Investment Environment in the Big Data Era - Duan, Xuqiang; Zhao, Xu; Liu, Jianye; Zhang, Shuquan; Luo, Dongkun (Frontiers in Energy Research, 2021)
Our research aims to analyze how various uncertainties and risks of overseas oil and gas investment environment change. The overseas risk assessment system has made great progress, however it has remained elusive due to great challenge of too many complex and interweaved factors. With the advent of big data and artificial intelligence era, more precise and specific risk evaluation can be conducted. Our research selects 25 indicators from six dimensions and applies Cloud parameter Bayesian network algorithm to dynamically assess oil and gas overseas investment risk of 10 typical resource countries, the results reveal risk dynamics over the past two decades. Our research is also significative to those outbound investment of investing, engineering and service projects. The properly use of risk assessment results can be conducive to those potential investors who will invest in potential countries in the future.